A Caenorhabditis elegans Zinc Finger Transcription Factor, ztf-6, Required for the Specification of a Dopamine Neuron-Producing Lineage. Issue 1 (1st January 2018) - Doitsidou, Maria; Minevich, Gregory; Kroll, Jason R; Soete, Gwen; Gowtham, Sriharsh; Korswagen, Hendrik C; Sebastiaan van Zon, Jeroen; Hobert, Oliver
Abstract: Invertebrate and vertebrate nervous systems generate different types of dopaminergic neurons in distinct parts of the brain. We have taken a genetic approach to understand how the four functionally related, but lineally unrelated, classes of dopaminergic neurons of the nematode Caenorhabditis elegans, located in distinct parts of its nervous system, are specified. We have identified several genes involved in the generation of a specific dopaminergic neuron type that is generated from the so-called postdeirid lineage, called PDE. Apart from classic proneural genes and components of the mediator complex, we identified a novel, previously uncharacterized zinc finger transcription factor, ztf-6 . Loss of ztf-6 has distinct effects in different dopamine neuron-producing neuronal lineages. In the postdeirid lineage, ztf-6 is required for proper cell division patterns and the proper distribution of a critical cell fate determinant, the POP-1 /TCF-like transcription factor.